THE INFLUENCE OF SMALL AND MEDIUM ENTERPRISE GROWTH, INVESTMENT, AND LABOR ON ECONOMIC GROWTH IN BATAM CITY - Intan Utna Sari; Asron Saputra (Universitas Putera Batam, 2020)
One of the important benchmarks in determining the success of economic development is economic growth. The role of the government in achieving development success is to determine the direction of development policies and to achieve these development targets a good development plan is needed to realize stable economic growth in order to improve people's welfare, namely by increasing Small and Medium Enterprises, Investment and Manpower. This study aims to determine the simultaneous and partial effect of Small and Medium Enterprises, Investment and Labor on the economic growth of Batam City. The data source is secondary data using panel data consisting of time series data for three years and cross section data of nine districts which resulted in 45 observations. The analysis technique used to solve the problem in this study is the multiple linear regression analysis model. The results of this study indicate that in terms of small and medium enterprises, investment and labor have a significant effect on economic growth in Batam City. This indicates that the number of SMEs (Small and Medium Enterprises), Investment and Manpower in Batam City can determine the level of economic growth in Batam City. This is because SMEs, investment and labor are activities that can produce goods or services. Partially Small and Medium Enterprises, Investment and Labor have a positive and significant effect on economic growth in Batam City, meaning that if the number of Small and Medium Enterprises, Investment and Labor is increased, economic growth will also increase.